M*A*S*H. Season eight [videorecording (DVD)] - Gelbart, Larry; Rappaport, John; Mulligan, Jim; Metcalfe, Burt; Alda, Alan, 1936-; Farrell, Mike; Swit, Loretta; Morgan, Harry, 1915-; Stiers, David Ogden; Farr, Jamie, 1934-; Christopher, William, 1932-; Burghoff, Gary (M*A*S*H DVD videorecording., 2005)
Television comedy about the experiences of military doctors and nurses working in a mobile army surgical hospital during the Korean War.